Bishop's hat silicene: A planar square silicon bilayer decorated with adatoms - Borlido, Pedro; Marques, Miguel A. L.; Botti, Silvana (Physical Chemistry Chemical Physics, 2021)
We investigate a family of free-standing quasi-two-dimensional silicon structures based on a planar square bilayer with adatom decorations. When attached to the bilayer, these adatoms form local reconstructions which resemble either a bishop's hat or elongated square bipyramids. We systematically constructed members of this family via exhaustive enumeration and then studied them using tight-binding and density-functional theory. We find that this geometry contributes significantly to the stability of the resulting structures, with some squared bilayers energetically more stable than the honeycomb bilayers. The most interesting phases were then characterized in more detail, and they all turned out metallic. Finally, we propose the [100] surface of ZrO2 as the most suitable substrate for the synthesis of these two-dimensional phases. This journal is
CRIS-Team Scopus Importer:2023-04-20